ESP NEEDS ANALYSIS OF FRONT OFFICE STAFF IN A HOTEL SETTING: A QUALITATIVE STUDY - Ambelina Henriques De Carvalho; Opirman Waruwu (Research on English Language Education, 2026)
The present research investigates the English for Specific Purposes (ESP) needs of front office staff at Neo Bintang Hotel, Sanur, Denpasar, Bali. Employing a qualitative descriptive case study approach, the research involved four front office staff members as primary participants, selected through purposive sampling. Data were collected through in-depth interviews, non-participant observation, and documentation analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three interconnected dimensions of ESP needs. First, in terms of target situation needs, front office staff are required to perform specific communicative tasks including greeting guests, managing reservations, handling complaints, and providing tourist information. Second, regarding present situation needs, a significant gap exists between the staff's current English proficiency and the communicative demands of their professional roles, particularly in speaking and writing skills. Third, concerning learning needs, participants expressed a strong preference for practical, task-based, and authentic hospitality materials. These findings underscore the urgent need for a targeted ESP program tailored to the specific communicative context of hotel front office work.